PENGARUH PELAPISAN PERMUKAAN PARTIKEL SiC DENGAN OKSIDA METAL TERHADAP MODULUS ELASTISITAS KOMPOSIT Al/SiC - Zainuri, M; Siradj, Eddy S; Priadi, Dedi; Zulfia, Anne; Darminto, Darminto (Makara Journal of Science, 2008)
The Influence of Coating Oxide Metal on Surface of SiC Particles to Elastic Modulus of Al/SiC Composites. The isotropic composites of Al/SiC is made by powder metallurgy method, the quality of mechanical materials depend on interfacial bonding between matrix (Al) and reinforcement (SiC). The quality of interfacial bonding can influence to elastic modulus of composites which is made by solid process. SiC particles were coated by metal oxide aim to enhance quality interfacial bonding between matrix and reinforcement. These research using three kinds of coating materials, which are Mg oxide, Cu oxide and Al oxide, and these materials were deposited on surface of SiC particles. From three kinds of materials coating Al2O3 is the best to enhance quality interfacial bonding between matrix and reinforce than the others as CuO or MgO. There is Intermetalic phase formatted on CuO coating, and MgO coating have many porous where they can make decrease quality of Al-SiC composites. All of volume fraction of SiC on the Al/SiC composites, which oxide aluminum coating on SiC surface have highest value of elastic modulus than the others metal oxides.